Human and murine neutrophils share core transcriptional programs in both homeostatic and inflamed contexts - Hackert, Nicolaj; Radtke, Felix A.; Exner, Tarik; Lorenz, Hanns-Martin; Müller-Tidow, Carsten; Nigrovic, Peter A.; Wabnitz, Guido H.; Grieshaber-Bouyer, Ricardo (bioRxiv beta, 2022)
Neutrophils are frequently studied in murine models, but the extent to which findings translate to humans remains poorly defined. Here, we performed an integrative transcriptomic analysis of 11 murine and 13 human datasets. In homeostasis, neutrophils exhibited the highest number of lineage-specific genes and the greatest degree of correlated expression among genes with one-to-one orthologs (r = 0.79, P < 2.2 × 10−16) compared to other leukocytes. In inflammation, neutrophils displayed considerable transcriptional diversity, but shared a core inflammation program across a broad range of conditions which was conserved between species. This core program included genes encoding IL-1 family members, CD14, IL-4R, CD69 and PD-L1. Chromatin accessibility of core inflammation genes increased significantly in blood compared to bone marrow and further with migration from blood to tissue. Transcription factor enrichment analysis nominated members of the NF-κB family and AP-1 complex as important drivers of the core inflammation program, and HoxB8 neutrophils with JUNB knockout showed a significantly reduced expression of core inflammation genes at baseline and upon stimulation. In vitro perturbations confirmed surface protein upregulation of core inflammation members in both species. Together, we demonstrate substantial transcriptional conservation in neutrophils in homeostasis and identify a core inflammation program conserved across species. This systems biology approach can be leveraged to improve transitions between the murine and human context. - Key PointsThe transcriptome of resting neutrophils is substantially conserved between humans and miceA core inflammation program in neutrophils is shared across a broad range of conditions and conserved across humans and mice - Download figureOpen in new tab